Keep oxygen in check: Contrasting effects of short-term aeration on hydrolytic versus oxidative enzymes in paddy soils. (June 2022) - Wang, Chaoqun; Blagodatskaya, Evgenia; Dippold, Michaela A.; Dorodnikov, Maxim
Abstract: Enzymes produced by microorganisms and plants are very sensitive to variations in soil microclimate, yet most enzyme assays are conducted under oxic conditions irrespective of the origin of environmental samples. It remains unclear how short-term aeration (minutes to hours) affects the hydrolytic and oxidative enzymes in anoxic systems. This key gap in current methods was addressed by measuring the kinetics of hydrolytic phosphomonoesterase, β-glucosidase, and leucine aminopeptidase and the activities of oxidative phenol oxidases and peroxidases by fluorogenic substrates under oxic (+O2 ) and anoxic conditions (–O2 ). Aeration effects were tested in a flooded paddy soil with growing rice (research task 1: moderate O2 limitation) and without rice (research task 2: strong O2 limitation). We tested two hypotheses explaining possible effects of short-term aeration on hydrolytic versus oxidative enzymes. (1) Aeration promotes Fe(II) oxidation, which leads to the accumulation of phenolics through the "iron-gate" mechanism, thus suppressing the activities of hydrolytic enzymes compared to the anoxic conditions. (2) Aeration stimulates phenol oxidases that degrade phenolics according to the "enzyme latch" concept, thus eliminating the suppression of hydrolytic enzymes. The activities of hydrolytic enzymes were lower by 5–43% in both experiments under + O2 compared to –O2 . In contrast, the activities of peroxidases and phenol oxidases were 2–14 times higher under + O2 than under –O2 . Thus, the activation of oxidative enzymes under + O2 was uncoupled from the hydrolytic activities. This contradicts both the "iron gate" and the "enzyme latch" mechanisms. We explain the short-term suppressive effect of O2 in assays by increased concentrations of reactive oxygen species, which decreased microbial activity. We conclude that our modification of enzyme assays under anoxic conditions is required for samples taken from low-oxygen environments to avoid underestimation due to rapid suppression of hydrolytic enzyme activities by O2 . Graphical abstract: Image 1 Highlights: O2 suppressed hydrolytic enzyme activities (Vmax ) up to 43% during 2.5 h of assays. Aeration increased the activities of phenol oxidases by 14 and peroxidases by 2 times. Short-term suppressive effect of O2 contradicted both "enzyme latch" and "iron gate". Enzyme activities in low-O2 ecosystems should be assayed under anoxic conditions.